Computationally motivated synthesis and enzyme kinetic evaluation of N-(β-d-glucopyranosyl)-1, 2, 4-triazolecarboxamides as glycogen phosphorylase inhibitors. Issue 1 (8th October 2014) - Begum, Jaida; Varga, Gergely; Docsa, Tibor; Gergely, Pál; Hayes, Joseph M.; Juhász, László; Somsák, László
Abstract : N -(β-d -Glucopyranosyl)-1, 2, 4-triazolecarboxamides discovered as low μM inhibitors of glycogen phosphorylase b. Abstract : Following our recent study of N -(β-d -glucopyranosyl)oxadiazolecarboxamides (Polyák et al., Biorg. Med. Chem. 2013, 21, 5738) revealed as moderate inhibitors of glycogen phosphorylase (GP), in silico docking calculations using Glide have been performed on N -(β-d -glucopyranosyl)-1, 2, 4-triazolecarboxamides with different aryl substituents predicting more favorable binding at GP. The ligands were subsequently synthesized in moderate yields using N -(2, 3, 4, 6-tetra- O -acetyl-β-D-glucopyranosyl)-tetrazole-5-carboxamide as starting material. Kinetics experiments against rabbit muscle glycogen phosphorylase b (RMGPb) revealed the ligands to be low μM GP inhibitors; the phenyl analogue ( K i = 1 μM) is one of the most potent N -(β-d -glucopyranosyl)-heteroaryl-carboxamide-type inhibitors of the GP catalytic site discovered to date. Based on QM and QM/MM calculations, the potency of the ligands is predicted to arise from favorable intra- and intermolecular hydrogen bonds formed by the most stable solution phase tautomeric (t2 ) state of the 1, 2, 4-triazole in a conformationally dynamic system. ADMET property predictions revealed the compounds to have promising pharmacokinetic properties without any toxicity. This study highlights the benefits of a computationally led approach to GP inhibitor design.